Effleurage Massage on the Intensity of Dismenorrhea in Adolescent Women ; Literature Review - Sari, Dewi Indah; Nurazizah, Nadia (Politeknik Kesehatan Kementerian Kesehatan Banten, 2023)
Background Dysmenorrhea is a menstrual condition that is accompanied by pain in the form of cramps in the abdomen which is caused by the increased production of prostaglandins. Young women who are experiencing dysmenorrhea may experience decreased activity and productivity whether in learning or working. Therefore, dysmenorrhea at the age of adolescence should be handled in order not to make a worse impact, one of the ways that can be done to decrease dysmenorrhea is massage effleurage. Purpose Knowing the intensity of dysmenorrhea in young women that given massage effleurage. Methods The research design used was a traditional review with compare method. selected the journals published from 2015 – 2020 about the effect of massage effleurage on the intensity of dysmenorrhea that was published on google scholar databases. Results The results of five journals that have been analyzed show that there are differences in the intensity of dysmenorrhea before and after giving massage effleurage, where the scale of dysmenorrhea in young women tends to decrease after giving massage effleurage. Conclusion Massage effleurage is effective to reduce the intensity of dysmenorrhea in young women.